Sijunzi decoction alleviates inflammation and intestinal epithelial barrier damage and modulates the gut microbiota in ulcerative colitis mice - Li, Hailun; Pu, Xing; Lin, Yongtao; Yu, Xinxin; Li, Jing; Bo, Lin; Wang, Hongwu; Xu, Yong; Li, Xiang; Zheng, Donghui (Frontiers in Pharmacology, 2024)
Ethnopharmacological relevance: As a representative classical prescription, Sijunzi Decoction has powerful therapeutic effects on spleen-stomach qi insufficiency. Ulcerative colitis (UC) is a chronic, diffuse, non-specifically inflammatory disorder of which the etiology still remains unclear. In the Traditional Chinese medicine (TCM) perspective, splenic asthenia is the primary cause of UC. Based on this, Sijunzi Decoction has been used extensively used in TCM clinical practice to alleviate UC in recent years. Whereas, the pharmacological mechanism of Sijunzi Decoction in modern medicine is still not completely clear, which limits its clinical application.The purpose of this study was to investigate the Sijunzi Decoction curative effect on acute UC mice and probe into its potential pharmacological mechanism.Materials and Methods: UC mice model was set up by freely intake of 3% dextran sulfate sodium (DSS) solution. The relieving role of Sijunzi Decoction on UC in mice was analyzed by evaluating the changes of clinical parameter, colonic morphology, histopathology, inflammatory factors content, intestinal epithelial barrier protein expression level and gut microbiota balance state. Finally, multivariate statistical analysis was conducted to lucubrate the relationship between inflammatory factors, intestinal epithelial barrier proteins and gut microbiota.Results: Firstly, the research findings revealed that Sijunzi Decoction could visibly ease the clinical manifestation of UC, lower the DAI score, and attenuate colonic damages. Moreover, Sijunzi Decoction could also significantly inhibit IL-6, IL-1β and TNF-α, while increase Occludin and ZO-1expression levels. Subsequently, further studies showed that Sijunzi Decoction could remodel gut microbiota homeostasis. Sijunzi Decoction was beneficial to regulate the content of Alistipes, Akkermansia, Lachnospiraceae_NK4A136_group and other bacteria. Finally, multivariate statistical analysis demonstrated that key gut microbes were closely associated with inflammatory factors and intestinal epithelial barrier proteins.Sijunzi Decoction can significantly prevent and treat UC. Its mechanism is strongly associated with the improvement of inflammation and intestinal epithelial barrier damage by regulating gut microbiota.